Ashura Ritual in Fadel Ilahi Eldimisky's Novel Muara Cinta - asnani sihotang (ITScience (Information Technology and Science), 2021)
The purpose of the research is to elaborate on the Ashura Ritual in Karbala, Irak. The primer data are quotations taken from Fadel Ilahi Eldimisky's novel Muara Cinta. The research is qualitative research related to social problems. Damono in Wiyatmi (2008) states that sociology is an approach in literary studies that understands and evaluates literary works by considering social aspects. In the Indonesian Dictionary, rituals are defined as matters relating to procedures in religious ceremonies. Ashura ritual is done every ten of Muharram, the month of the Hijri lunar calendar. It is celebrated all over the world. In Karbala, Irak, the ritual has been performed by Shiah. The Ashura rituals found in Karbala are the ritual of beating the chest, hitting the back with a chain, and hurting the head and body. All the findings are analyzed in the discussion.